2021
DOI: 10.3390/healthcare9091133
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Users of Online Mental Health Communities Get Likes and Reposts: A Combination of Text Mining and Empirical Analysis

Abstract: An online community is one of the important ways for people with mental disorders to receive assistance and obtain support. This study aims to help users with mental disorders to obtain more support and communication through online communities, and to provide community managers with the possible influence mechanisms based on the information adoption model. We obtained a total of 49,047 posts of an online mental health communities in China, over a 40-day period. Then we used a combination of text mining and emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Sarma et al [ 36 ] observed that user like reactions were not useful in ranking informative comments on the Twitter platform [ 68 ]. In line with previous studies, despite higher coverage, the like reaction of the whole community might not be a reliable indicator of the overall usefulness of a resource in NOCC [ 69 - 71 ]. Furthermore, a like reaction from the original user with the question could serve as an indicator of resource relevance; however, the low coverage of these likes (at maximum 3/85, 4% for relevant resources) makes it difficult to use this source of feedback in practice for finding relevant resources.…”
Section: Discussionsupporting
confidence: 61%
“…Sarma et al [ 36 ] observed that user like reactions were not useful in ranking informative comments on the Twitter platform [ 68 ]. In line with previous studies, despite higher coverage, the like reaction of the whole community might not be a reliable indicator of the overall usefulness of a resource in NOCC [ 69 - 71 ]. Furthermore, a like reaction from the original user with the question could serve as an indicator of resource relevance; however, the low coverage of these likes (at maximum 3/85, 4% for relevant resources) makes it difficult to use this source of feedback in practice for finding relevant resources.…”
Section: Discussionsupporting
confidence: 61%
“…We first tested the direct effects of the six themes on PDM to reveal how patients' perceived physician warmth and perceived competence affect potential PDM, constructing the model (Model 1) as follows: Where the independent variable denotes the proportion of topic k in comment i, k ∈ [ [1] , [2] , [3] , [4] , [5] , [6] ]. The value of can be output through the stm package in the R programming tool.…”
Section: Analysis and Findingmentioning
confidence: 99%
“…Physicians can provide patients with a wide range of healthcare services virtually through online health communities [ 3 ]. Patients can receive emotional and informational support through online health communities [ 4 ]. The process of the patient visit includes at least three steps: the patient's choice, the patient's interaction with the physician, and the patient's feedback to the physician.…”
Section: Introductionmentioning
confidence: 99%
“…Users’ participation is a critical index of OHCs ( Bennett-Levy et al, 2021 ; Liu and Kong, 2021 ). OHCs can provide medical and health care service consumers with instant access to information, massive medical care information, and other medical and health care services ( Loane et al, 2015 ; Lu et al, 2020 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%